Immunohistochemical expression of p16INK4a in premalignant lesions and malignant tumours of cervix - Sandhu, Parminder J. S.; Nibhoria, Sarita; Sandhu, Vaneet K.; Kaur, Harpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical carcinoma is the third most common cancer in women worldwide and firth most common cause of cancer related deaths. Human Papilloma virus, the most common cause of cervical cancer, causes functional inactivation of pRb, resulting in overexpression of p16INK4a. The overexpression of p16INK4a correlates well with the degree of cervical dysplasia and neoplasia. The present study is done to determine the IHC expression of p16INK4a so that it may be used as a biomarker for HPV and may play a role in the prevention, diagnosis and prognosis of cervical neoplasm. Methods: The present study was conducted on 60 formalin-fixed, paraffin-embedded specimens of cervical neoplasms, which comprised 47 cases of squamous cell carcinoma followed by 8 cases of adenocarcinoma, 3 cases of HSIL and 2 cases of LSIL. These were then subjected to IHC by p16INK4a. Cytoplasmic and nuclear positivity for p16INK4a was noted. Results: Overall 95% cases were positive for p16INK4a expression, 100% cases of adenocarcinoma, 98% cases of squamous cell carcinoma, 100% cases of HSIL and 0% cases of LSIL were positive for p16 expression. Conclusions: The present study showed statistical correlation of immunoreactivity of p16INK4a with histological type was clinically significant (p value <0.0001). In our study, p16INK4a immunohistochemical expression increased with increasing degree of dysplasia and with presence of cervical carcinoma.